A clinical review and history of pubic lice. (12th May 2021) - Patel, P. U.; Tan, A.; Levell, N. J.
Summary: The ectoparasite Pthirus pubis (PtP), commonly known as the crab or pubic louse, has plagued primates from prehistoric apes to Homo sapiens . We combed the literature from antiquity to the present day, reviewing the pubic louse's origins, its evolution with mankind, and its presentation and management. MEDLINE and EMBASE provided the greatest yield of literature compared with other databases. Estimates for PtP incidence range from 0.3% to 4.6% and for prevalence around 2% in adults. War, disasters and overcrowding support lice transmission, but modern pubic hair grooming has reduced the incidence of PtP in recent years. PtP, is usually found on pubic hair, but may infest scalp and body hair, eyebrows and eyelashes. Reports suggest the possibility of PtP as a vector for Bartonella spp. and Acinetobacter spp., which require further study. Transmission of PtP is via close contact, so sexual abuse and concomitant sexually transmitted infections should be considered. Symptoms and signs of infestation include pruritus, red papules and rust/brown deposits from feeding or faecal matter. Visualization of live lice confirms the diagnosis. Traditional treatments include hand‐picking and combing, but in modern times pediculicidal products may generate faster resolution. Permethrin or pyrethrins are the first‐line recommendations. Resistance to pediculicides is common with head lice and is presumed likely with PtP, although data are lacking. Pseudoresistance occurs as a result of poor compliance, incorrect or ineffective dosing, and reinfestation. In true resistance, a different pediculicide class should be used, e.g. second‐line agents such as phenothrin, malathion or ivermectin. Lice have existed long before humans and given their adaptability, despite habitat challenges from fashion trends in body hair removal, are likely to continue to survive. Abstract : Click here for the corresponding questions to this CME article.